The Ignatian Discernment Approach in Building the Identity of Catholic - Gowasa, Ricardo Putrawan; Famaugu, Hendra (Studia Philosophica et Theologica, 2025)
Discernment is an important tool in forming the identity of Catholic Young People (OMK) amidst the challenges of modernity characterized by secularism, individualism, and materialism. The influence of modernization and globalization makes it difficult for OMK to find their identity. In this context, they often experience confusion and an identity crisis, especially when they have to choose between different value cultures. A crisis of values, morals, and role models often clouds the direction of young people’s lives. This article explores the role of discernment in helping OMK recognize their calling in life, discern God’s will, and build an authentic relationship with God. Using an Ignatian approach, discernment is described as a means of sorting out the movements of the spirit, understanding consolation and desolation, and integrating Christian values in decision-making. This article employs a literature review approach covering sources from spiritual theology, youth studies, and pastoral approaches to analyze the impact of social, technological, and materialistic cultural changes on the identity crisis of OMK. The article emphasizes the importance of parents’ roles in modeling and transmitting the Catholic faith, spiritual accompaniment, contextualized faith education, utilization of digital media, and experiences of encounter through social action to help OMK build a Christian identity amid the challenges of secularism and digitalization.